Antifungal activity of indolicidin-derived peptide In-58 against Sporothrix globosa in vitro and in vivo - Li, Sushan; Tang, Zhanhan; Liu, Zhe; Lv, Sha; Yao, Chunli; Wang, Shuang; Li, Fuqiu (Frontiers in Medicine, 2024)
In-58, a peptide derived from indolicidin, shows extraordinary antibacterial activity and lower toxicity than indolicidin toward mammalian cells. Here, we investigated the antifungal activity of In-58 against the human pathogen Sporothrix globosa in vitro and in vivo. In-58 markedly inhibited the growth of S. globosa isolates in microdilution assays and showed no antagonism with any tested antifungal agent (itraconazole, terbinafine or amphotericin B). Scanning electron microscopy and propidium iodide staining indicated that In-58 alters the cell wall integrity and interacts with DNA, leading to disruption of S. globosa in a dose-dependent manner. In S. globosa, the mitochondrial membrane potential decreased and reactive oxygen species increased after treatment with In-58. In vivo experiments in the Galleria mellonella (greater wax moth) larval infection model revealed the effectiveness of In-58 against S. globosa infection with low toxicity. Our results indicate that In-58 possesses remarkable antifungal activity against S. globosa in vitro and in vivo. It has potential as a novel drug for the treatment of sporotrichosis.88 2.1. Fungal Strains and Culture 89 Fungal strains were isolated from patients diagnosed with sporotrichosis in The